Efektivitas Pemeriksaan, Penagihan Pajak dengan Surat Paksa dalam Rangka Meningkatkan Penerimaan PPN Pada KPP Pratama Banjarmasin - Fatimah Fatimah; Kasyful Anwar; Ayu Oktaviani (Journal of Applied Accounting and Taxation, 2019)
The purpose of this study to analyze the effectiveness of the examination, collection with forced letters to increase VAT receipts at KPP Pratama Banjarmasin from 2013-2017.This study uses a descriptive method describing the data processed and analyzed qualitatively based on realization data and comparison targets, with a standard reference of the specified indicators.The results of the analysis of the implementation of VAT audits at KPP Pratama Banjarmasin in 2013, 2015 and 2016 were less effective. 2014 is quite effective and 2017 has been effective. Some of the issuance of the SP2 is issued at the end of the year and may not be completed in the year concerned. The extent of the examination and data on taxpayers have not been maximally fulfilled so that they require a long inspection period. The implementation of tax collection with a forced letter of value-added in 2013-2016 was dominated by ineffective indicators both in terms of the number of forced letters submitted and the nominal amount. Based on the forced letters issued in that year all can not be conveyed by the bailiff due to difficulty identifying or finding the address of the taxpayer and it is not yet clear. The effectiveness of 2017 in terms of absolute shows very effective criteria. The tax authorities carry out active collection of forced letters issued in 2017. Then new regulations PMK 165 / PMK.03 / 2017 are issued regarding tax arrears or calculation of unpaid tax payable at the prescribed rates. Then the taxpayer is more cooperative in paying his tax debt.